Manajemen Kepala Sekolah dalam Penguatan Pendidikan Karakter di SD Insan Mandiri Bandar Lampung - Tri Mulyanto; Nanda Dwi Rohmah; Arum Agustriana (Al-fahim : Jurnal Manajemen Pendidikan Islam, 2021)
The research was conducted at SD Insan Mandiri Bandar Lampung to see how principal manages the school to enhance character education. The background in this study was based on the massive influence of Western culture which has caused a multidimensional crisis in various circles of the education world. This type of research is field research with a descriptive approach. The data of this study were collected through observation data, interviews and documentation. Data analysis in this study was carried out continuously. The results of the data obtained are selected, then categorized between similar data and then analyzed critically and objectively. Data analysis was carried out in three stages, namely data reduction, data display and drawing conclusions. This study reports that 1) the principal of school management in character education is shown by integrating various approaches, such as the formal approach, the school culture approach, the paradigmatic approach and the habitual approach. In its implementation the principal integrates all approaches with intracurricular, co-curricular and extracurricular activities in the form of Islamic culture, such as 5s activities, calligraphy, memorization of short letters, memorizing selected hadiths, recitation, duha prayer, midday prayer and Asr prayer simultaneously which experience with prayer. 2) the values ​​that are implemented in the form of improving character education including religiosity, integrity, independence and mutual cooperation.